Mild Cognitive Impairment - Shalihin, Mohd Shaiful Ehsan; Wan Mamat, Wan Hasliza; Mohamad Zahir, Mohd Zulkifli; Mohammad Aidid, Edre (2021)
This slide presentation is for education and training in the workshop series regarding Mild Cognitive Impairment and Prevention of Dementia in any geriatric centre. Therefore, it can be used as a reference by any researcher involved with geriatric care.